Ginkgolide B as a biopsychosocial treatment salvages repeated restraint stress-induced amygdalar anomalies in mice - Olusegun G. Adebayo; Benneth Ben-Azu; Wadioni Aduema; Oyetola T. Oyebanjo; Emmanuel U. Modo; Iheagwam Pauline Ndidiamaka; Spiff E. Eleazer; Joseph Igbo Enya; Abayomi M. Ajayi (IBRO Neuroscience Reports, 2025)
From preclinical and clinical findings, it has been shown that the amygdala is a critical mediator of stress and primary target for stress effects in the brain. We investigated the neuroprotective effect of Ginkgolide B (GB) in repeated restraint stress-induced behavioral deficit and amygdalar inflammation in mice. Mice were orally pre-treated with GB 20 mg/kg 1 h prior to 4 h restraint stress for 21 consecutive days. Behavioural deficit and serum and amygdalar biochemical changes were estimated using spectrophotometric and ELISA techniques. The results showed that GB pre-treatment inhibited spatial memory deficit, renounces neuropsychiatric phenotypes and metabolic redox activity by augmenting the endogenous antioxidant system via Nrf2 levels in the mice. The HPA axis activity impaired by the restraint stress induction was abated with marked reduction of corticosterone, hypertrophy of the adrenal gland and blood glucose level. Meanwhile, our data further reveals that GB pre-treatment inhibited the release of neuroinflammatory mediators (MPO, TNF-α, IL-6, MAPK, COX-2) and elevated CREB production via activation of BDNF protein. Further, the acetylcholinesterase activity was inhibited while the level of glutamate release remains unchanged in the amygdala of the restraint mice. The GB treatment also up-regulate the release of BCL-2 proteins. This study suggests that GB could be considered as a therapeutic agent in the management of memory impairment, neuropsychiatric phenotypes and neuropathological alterations.